A Comparison of Robot-Assisted Laparoscopic Ureteral Reimplantation and Conventional Laparoscopic Ureteral Reimplantation for the Management of Benign Distal Ureteral Stricture - Zhang, Yucong; Ouyang, Wei; Xu, Hao; Luan, Yang; Yang, Jun; Lu, Yuchao; Hu, Jia; Liu, Zheng; Yu, Xiao; Guan, Wei; Hu, Zhiquan; Wang, Shaogang; et al. (Urology Journal, 2020)
Purpose: To describe our experience and analyze the outcomes of robot-assisted laparoscopic ureteral reimplantation (RALUR) and conventional laparoscopic ureteral reimplantation (LUR) in treating benign distal ureteral stricture (DUS). Material and Methods: Patients who underwent RALUR or LUR for DUS were retrospectively analyzed. All surgeries were performed by transperitoneal approach in a refluxing manner. Baseline characteristics, history of previous abdominal surgery, operative profile and follow-up data were collected and analyzed. Results: Among 68 patients with DUS, 62 were diagnosed with unilateral DUS, including 28 patients underwent RALUR. The mean operative time of the RALUR group was 2.44 ± .45 hours, while the mean operative time of the LUR group was 3.09 ± .74 hours (P < .001). The average suturing time of LUR (39.59 ± 3.78 min) is about 2 times that of RALUR (20.04 ± 3.5 min) (P < .001). The success rate of the RALUR group and the LUR group were 89.3% and 82.4% respectively (P = .494). In multiple linear regression model, the modality of surgery was the only variable that influences operative time (Beta = -.964, P < .001), suturing time (Beta = -1.899, P < .001) and hemoglobin decline (Beta = -.611, P = .020). Conclusion: Basically, the postoperative outcomes are similar but robotic surgery offers a quicker surgery and anastomosis.